2016
DOI: 10.1063/1.4966283
|View full text |Cite
|
Sign up to set email alerts
|

High current density 2D/3D MoS2/GaN Esaki tunnel diodes

Abstract: KEYWORDSMoS 2 , tunnel diode, GaN, 2D/3D heterojunction, interband tunneling.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
56
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 37 publications
1
56
0
1
Order By: Relevance
“…9,10 Recent advances in the integration of 2D-layered materials with wide band gap group-III nitride semiconductors are exciting due to their variety of applications in high current tunnel diodes. [11][12][13] In this context, several efforts were made to grow GaN on closely lattice matched TMDs. Yamada et al reported the growth of GaN on bulk MoS 2 by plasma-enhanced molecular beam epitaxy (MBE).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Recent advances in the integration of 2D-layered materials with wide band gap group-III nitride semiconductors are exciting due to their variety of applications in high current tunnel diodes. [11][12][13] In this context, several efforts were made to grow GaN on closely lattice matched TMDs. Yamada et al reported the growth of GaN on bulk MoS 2 by plasma-enhanced molecular beam epitaxy (MBE).…”
mentioning
confidence: 99%
“…14 22,23 In spite of the smaller in-plane lattice mismatch (%0.8%) of GaN with MoS 2 , 15 the type-II heterojunction formed by them can be solely utilized for electronic devices. [11][12][13] In contrast, optoelectronic devices formed by 2D/ 3D heterojunctions require a type-I band alignment which can be realized by using the group III-nitride alloys with higher bandgap as a constituent semiconducting layer of the 2D/3D heterojunction. Thus, In x Al 1-x N with a low In composition (12%-18%) exhibiting higher bandgap (>4.5 eV) and lattice matched to the MoS 2 layer with high contrast of the refractive index (%30%) may be employed to achieve the type-I 2D/3D junction.…”
mentioning
confidence: 99%
“…Further, we observe the ideality factor of GaN-MoS 2 diodes (1.5 < n < 2.0) is smaller than that of Si-MoS 2 diodes (2.0 < n < 3.5) because, in contrast to GaN, Si surface has a thin native oxide layer which degrades interface quality of 2D/3D junction (Figure 4d, Figure S3, Figure S15 in SI). 26,[44][45] Despite the differences in quality of the interface, the gate-tunability of rectification ratio maintains the same trend (Figure 4e, red plot) and the rectification ratio reaches a maximum when the MoS 2 is fully depleted suggesting a maximum in built-in potential and formation an n ++ /i junction. Likewise, a high asymmetry is observed in gate-dependent conductance (transfer characteristics) depending on whether the diode is forward biased (-V DS ) versus reverse biased (+V DS ).…”
Section: Resultsmentioning
confidence: 80%
“…7,23 Other approaches have been limited to exploiting lowpower operation or tunneling phenomena and photoresponse in two-terminal devices. [24][25][26][27][28][29] Overall, the advantage of using ultrathin 2D materials and exploiting their field tunability has not been systematically investigated and exploited.…”
Section: Introductionmentioning
confidence: 99%
“…2D materials can also be synthesized in a variety of compositions and structures, consequently resulting in novel properties at the interface that are not limited to the structural constraints in conventional interfaces, such as the choice of substrate and strain/defect control. Large area growth and/or transfer of 2D films have been extensively studied lately, most notably using metaldichalcogenides systems [1]. Here, we present the cross-sectional atomic scale imaging and analysis of GaSe 2D layered materials on GaN substrate using scanning transmission electron microscopy (STEM) [2].…”
mentioning
confidence: 99%